(untitled) (Journal of Fiber Bioengineering and Informatics, 2023)
Biomedical stents for the digestive tract address many of the limitations associated with traditional surgical treatments for gastrointestinal diseases. This paper provides a review of the performance requirements, complications, and limitations of stent materials in the treatment of common digestive tract diseases. The advantages and disadvantages of different materials and processing technologies for digestive tract stents are discussed. Furthermore, considering the diverse requirements for ideal alimentary canal stent materials, the challenges that require further research are outlined in detail, providing strategic references for the development of biomedical stents for the digestive tract.